Gestational diabetes and its impacts on pregnancy, childbirth and puerperium - Matos, Gabriel Barbosa de (Seven Editora, 2023)
Gestational diabetes is a significant concern for women during the gestational period, triggering metabolic dysfunctions and substantial changes. The general objective of this study is to understand the approaches adopted by family health professionals to reduce the incidence of diabetes during pregnancy, focusing on the influence of lifestyle change (SEM) and the provision of appropriate guidelines for the provision of effective care to this specific group of patients. The methodology adopted for this research comprised an integrative literature review, of a quantitative nature. This methodological approach seeks to analyze and identify knowledge produced related to the topic in question, aiming to deepen and adapt the available theoretical basis. During the review, 6 publications in Portuguese and 9 in English were considered, addressing different aspects of effectiveness in primary prevention, prophylactic measures, consequences of drug use, and the role of nurses in prevention and care. The discussions and results obtained focus on the need for targeted strategies to deal with the complications associated with gestational diabetes during pregnancy, highlighting the appropriate approach for affected newborns. The study emphasizes the importance of professional support in the face of clinical complications resulting from gestational diabetes, especially in situations of cyanosis and breathing difficulties after childbirth, emphasizing the importance of oxygen therapy to enable lung expansion and hematosis. DOI:https://doi.org/10.56238/sevened2023.004-026